Providing cow-assisted therapy in the context of Polish realities - Szczucka, Ewa (Turystyka i Rozwój Regionalny, 2024)
Cow-assisted therapy is one of the forms of bovine-assisted therapy, which is used to improve well-being and as a treatment for numerous diseases and disorders. Despite its growing popularity around the world, it remains relatively unknown in Poland. Cow-assisted therapy can be a good basis for diversifying the activities of cattle breeders. The purpose of the study is to identify the determinants of the provision of a cow-based health support service in Poland. The method used is a case study. The object under study is located in the warmińsko-mazurskie voivodeship and is one of the few places in Poland offering therapy with cows. It is also a facility that offers the purchase of animals trained for bovine-assisted therapy. There are barriers limiting the development of therapy with cows in Poland. Among the most important of these are cultural, climatic, financial, personnel and time barriers.